If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + -1x = 4x + -60 Reorder the terms: 5 + -1x = -60 + 4x Solving 5 + -1x = -60 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 5 + -1x + -4x = -60 + 4x + -4x Combine like terms: -1x + -4x = -5x 5 + -5x = -60 + 4x + -4x Combine like terms: 4x + -4x = 0 5 + -5x = -60 + 0 5 + -5x = -60 Add '-5' to each side of the equation. 5 + -5 + -5x = -60 + -5 Combine like terms: 5 + -5 = 0 0 + -5x = -60 + -5 -5x = -60 + -5 Combine like terms: -60 + -5 = -65 -5x = -65 Divide each side by '-5'. x = 13 Simplifying x = 13
| 7x-2x=8-3x | | 3x+8=-4x+8 | | -4x-1=-1+7x | | 4x-12=-7x+10 | | 5x-x=3x-2 | | -x+3=23 | | -2x-6=16 | | x^3-12= | | 7x-(3x+6)=5x-47 | | 5x^2+1=2x | | 2y^3-7y^2+3=0 | | 50x^2+1=2x | | 6x-7x-5=0 | | 16x-282=6x-12 | | 52-6x=12x+18 | | 9x-(7x+2)=3x-22 | | 6x+22=16x-98 | | 3x^2+2x-40=0 | | 3x^2+58x-40=0 | | 3x^2+119x-40=0 | | x^2+25x-24=0 | | 2x+125=6x+93 | | (x)(x+1)(x+2)=720 | | 2x+25=6x+93 | | 3x^2-29x-10=0 | | x^4-4x^2+12x+9= | | x^4-4x^2+12x+9=0 | | 3x+2.3=5x+1.7 | | (3x-2)(x^2-6x+1)=0 | | a*12=b | | 5x+15=70 | | 4x^2-300=0 |